MORPHOLOGICAL, STRUCTURAL, MICROHARDNESS AND ELECTROCHEMICAL CHARACTERIZATIONS OF ELECTRODEPOSITED Cr AND Ni–W COATINGS - Elkhanssa Aidaoui; Hachemi Ben Temam; Okba Belahssen; El Hachmi Guettaf Temam (Acta Metallurgica Slovaca, 2018)
Currently, Ni-Cr coatings are widely used in a number of important applications due to their excellent properties. In this study, Ni-Cr alloys were electrodeposited from citrate bath onto Cu substrates by using different values of applied current densities. The effects of plating deposition current density on morphological and structural characterization of Ni-Cr electrodeposited coatings were investigated by means of scanning electron microscopy (SEM) and X-ray diffraction (XRD). Microhardness of the coatings is also evaluated using Vickers’s microhardness. Potentio-dynamic polarization and electrochemical impedance spectroscopy (EIS) tests in 3.5 wt % NaCl solution were used to evaluate corrosion résistance of Ni-Cr coatings. The results showed that the surface morphology of the all coatings contained micro cracks and pores. XRD patterns indicate the formation of Ni-Cr and Cr3Ni2 phases. Microhardness measurements show that all Ni-Cr samples are harder than copper substrate. Electrochemical tests show that 3 A.dm-² is an optimal value of applied current density in the sense of the least value of Ecorr = -12.3 mV and the best charge transfer resistance Rp = 303.03 Ω.cm².